Pandemic Exposure, Post-traumatic Stress Disorder, Conflict Behaviors, and Online Aggressive Behaviors Among College Students During the COVID-19 Pandemic: Examining the Moderating Role of Gender - Zhen, Baohua; Yao, Benxian; Zhou, Xiao (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic impacts people’s mental health and behaviors, but the influence mechanism between pandemic exposure, conflict behaviors, and online aggressive behaviors during the COVID-19 outbreak remains unclear. This study will address this gap. Data were collected from 1153 college students in an online survey that included an pandemic experiences scale, a PTSD scale, a conflict behaviors scale, and an online aggressive behaviors scale. Structural equation modeling and multi-group comparisons were used to analyze the data. Pandemic exposure positively predicted conflict and online aggressive behaviors through hyperarousal symptoms, and negatively predicted these behaviors through intrusive symptoms. The mediating roles of avoidance and negative alterations in cognition and mood symptoms in the relations between pandemic exposure and conflict behaviors and online aggressive behaviors were non-significant. Among male students, pandemic exposure directly predicted conflict and online aggressive behaviors, but for female students, pandemic exposure indirectly influenced these behaviors through intrusive and hyperarousal symptoms. The intrusive and hyperarousal symptoms play mediating roles in the relations between pandemic exposure and conflict behaviors and online aggressive behaviors. Gender plays a moderating role in the above mediating mechanism.